Clinical and Sociodemographic Characteristics that May Affect Delays in Child Sexual Abuse Disclosures: Ten Years in Practice - Hicran Doğru; İbrahim Selçuk Esin; Ahmet Nezih Kök; Onur Burak Dursun (Eurasian Journal of Medicine)
Background: This study covers Child Sexual Abuse (CSA) survivors who had never disclosed the abuse until their psychiatric interview. There is a clear lack of understanding of which factors contribute to delays in the disclosure of CSA. Thus, we aimed to examine the risk factors and sociodemographic variables that may inhibit CSA disclosures.